2016
DOI: 10.33830/jom.v12i1.22.2016
|View full text |Cite
|
Sign up to set email alerts
|

Efek Pengukuran Keuangan Dan Non Keuangan Terhadap Kinerja: Pandangan Teori Penetapan Tujuan

Abstract: The aim of this study tested the effects of the perception of fairness measure for assessing performance against the performance of the mediation of impact, competence and self-determination as an aspect of empowerment. This research uses experimental studies as a method of data collection by providing a variable size treatmen on performance measurement with the difficulty level objectives and the level of difficulty of the task. Experimental design used 2 x 2 x 2 between subjects.   Results from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Locke and Latham (1990) stated that challenging goals would be a challenge for individuals to achieve them when they are clearly defined. Klein and Daniel (1990), Arsanti ( 2009), Murniati et al (2016), Wallace andEtkin (2017), andJustin et al 2017 found that the level of difficulty and clarity of goals affect individual performance. Individuals who have clear goals with a high level of difficulty will encourage individuals to plan, identify what is needed and determine strategies to achieve these goals.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Locke and Latham (1990) stated that challenging goals would be a challenge for individuals to achieve them when they are clearly defined. Klein and Daniel (1990), Arsanti ( 2009), Murniati et al (2016), Wallace andEtkin (2017), andJustin et al 2017 found that the level of difficulty and clarity of goals affect individual performance. Individuals who have clear goals with a high level of difficulty will encourage individuals to plan, identify what is needed and determine strategies to achieve these goals.…”
Section: Hypothesis Developmentmentioning
confidence: 99%